Acute and Subacute Toxicity Evaluation of the Stem Bark Aqueous Extract of Harungana Madagascariensis in Rodents - Ngo Lemba Tom, Esther; Nyemb, Nyunaї; Kouem, Gbaangne Djaouro; Mba Medou, Fabrice; Diane Nankia, Florette; Dimo, Théophile (Journal of Advanced Pharmaceutical Science And Technology, 2018)
The present investigation was carried out to evaluate the safety of a stem bark aqueous extract of Harunganamadagascariensis Lam. (Hypericaceae) by determining its potential toxicity after acute and subacute administration in rodents. Acute toxicity tests were carried out in mice and the behavior, death and median lethal dose (LD50) were estimated. Subacute toxicity (28 days) studies were conducted in rats with oral daily doses of 200, 400 and 600 mg/kg. Parameters observed at the end of the subacute tests included changes in body and vital organ weights, mortality, hematological, biochemical, hepatic and kidney effects. Harunganamadagascariensisextract did not produce any visible toxicity or mortality with oral doses up to 2000 mg/kg within 14 days of single treatment, leading to the conclusion that the LD50 is greater than 2000 mg/kg. In the subacute toxicity tests, neither mortality nor visible signs of lethality was seen in rats. No significant change in the weight of the kidney, liver, heart, lungs spleen, pancreas and testicles was observed. Alanine transaminase (ALT) increased significantly in males at 400 and 600 mg/kg, whereas Aspartate transaminase (AST) decreased at 600 mg/kg in female rats. HDL Cholesterol was reduced at 600 mg/kg in female rats. There was a significant increase in urea concentration in female rats at 400 mg/kg. A significant decrease, both in platelet volume distribution (PVD) at 400 mg/kg in male rats and in red cell volume distribution (RDW) at 200 mg/kg were recorded in female rats respectively, but with no changes in other hematologic parameters. Histological study shows normal structure of liver, kidneys and heart of control and treated rats. Results indicate that oral doses of aqueous stem bark of Harunganamadagascariensis are relatively safe in rats; however, assessment of hepatobiliary function should be done during chronic use in humans.
Keywords: Harungana madagascariensis; acute; subacute; toxicity; biochemistry; Hypericaceae.